Relationship of Price, Product Quality, Service Quality, Environment, and Customer Satisfaction: An Empirical Evidence of A Waroeng Campus Nasi Bajet, Shah Alam, Selangor - Zahro, Nur Fatimatuz; Abdul Jamal, Yuhanis Binti (Journal of International Accounting, Taxation and Information Systems, 2024)
This research aims to explore whether there is a relationship between price, product quality, service quality, environment, and customer satisfaction at the budget rice campus stall. It is very important to know the relationship between price, product quality, service quality, environment, and customer satisfaction at this restaurant. The level of competition is so tight that customer satisfaction is the top priority so that a business can compete and even dominate market share. This research involved eating places in Shah Alam, Syeksen 13 that volunteered to participate in this research with a sample of 150 customers who had visited to the restaurant at least once. the data analyzed using descriptive statistics with utilized online questionnaire distribution and IBM Statistical Package for Social Sciences (SPSS) Version 29.0 for data collection. Purposive sampling was used to target relevant professions and employees of the selected organizations. using convenience sampling methodology was used for collecting the data from respondents. Furthermore, this study shows the restaurant's ability to satisfy its patrons is positively and significantly correlated with its service quality, food quality, pricing, and physical surroundings. The most important conclusion from this research is that there is a fairly significant positive relationship between price, product quality, service quality, environment, and customer satisfaction in this restaurant with an r value of 0.339* (p<0.01) and above, which shows that it shows how one variable influences other variables in this research. These findings' implication that eateries should concentrate more on their resources and enhance the quality of their food, services, and products, all of which can raise customer satisfaction levels.